Are eruptions reliable precursors to marine volcano collapses? - Furst, Séverine; Urlaub, Morelia; Klein, Elisa; Bonanati, Christina (Frontiers in Earth Science, 2023)
Volcanoes are sources of numerous threats including lava flows, pyroclastic flows, ash dispersal and landslides or sector collapses. In addition to these common volcanic hazards, volcano-induced tsunamis can occur in the marine environment, introducing a major hazard that can affect populations far away from the volcanoes. Tsunami warning systems are not designed to include volcano-generated tsunamis, partly due to a lack of knowledge of precursory signals and also because such signals will have to be detected nearby rather than remotely. The majority of historically documented volcano collapses occurred at erupting volcanoes, which may suggest that eruptions could be a potential warning signal and that erupting volcanoes are more likely to produce collapses. In this perspective paper we confront this paradigm by in-depth examinations of historic examples, examples from the geological records and theoretical considerations, and highlight the need for a more robust understanding of precursors to volcano collapse in marine environment.